Cardiopulmonary Resuscitation in Infants and Children With Cardiac Disease: A Scientific Statement From the American Heart Association. Issue 22 (29th May 2018) - Marino, Bradley S.; Tabbutt, Sarah; MacLaren, Graeme; Hazinski, Mary Fran; Adatia, Ian; Atkins, Dianne L.; Checchia, Paul A.; DeCaen, Allan; Fink, Ericka L.; Hoffman, George M.; Jefferies, John L.; Kleinman, Monica; et al.
Abstract : Cardiac arrest occurs at a higher rate in children with heart disease than in healthy children. Pediatric basic life support and advanced life support guidelines focus on delivering high-quality resuscitation in children with normal hearts. The complexity and variability in pediatric heart disease pose unique challenges during resuscitation. A writing group appointed by the American Heart Association reviewed the literature addressing resuscitation in children with heart disease. MEDLINE and Google Scholar databases were searched from 1966 to 2015, cross-referencing pediatric heart disease with pertinent resuscitation search terms. The American College of Cardiology/American Heart Association classification of recommendations and levels of evidence for practice guidelines were used. The recommendations in this statement concur with the critical components of the 2015 American Heart Association pediatric basic life support and pediatric advanced life support guidelines and are meant to serve as a resuscitation supplement. This statement is meant for caregivers of children with heart disease in the prehospital and in-hospital settings. Understanding the anatomy and physiology of the high-risk pediatric cardiac population will promote early recognition and treatment of decompensation to prevent cardiac arrest, increase survival from cardiac arrest by providing high-quality resuscitations, and improve outcomes with postresuscitation care.